Analisis Tingkat Kejenuhan Belajar Fisika pada Pembelajaran Daring di SMA YPK Oikoumene Masa Pandemi Covid-19 - Desi Yunisari Tutuala; Sri Wahyu Widyaningsih; Kaleb A Yenusi; Irfan Yusuf (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to analyze the level of learning saturation of students at SMA YPK Oikoumene in online learning. The research method used in this study is a survey method using a questionnaire. The sampling technique used was purposive sampling, with a sample of 60 students from class X and XI science. The instrument used in this study was a learning saturation level questionnaire consisting of 15 statements. The results of the analysis show that the level of learning saturation in students belongs to four categories, namely 1) very saturated 10%, 2) 60% saturated, 3) moderately saturated 27% and 4) unsaturated 3%. While the level of saturation shown by YPK Oikoumene High School students is the saturation caused by very monotonous learning. The results of the analysis using the Rasch model are 1). The analysis carried out on the person there is one student with a very high level of saturation and two students with a very low level of saturation. 2). The analysis carried out on items, the statement with the highest logit value is the statement with the code P1 and the lowest is the statement with the code P15.